Edukasi Periode Emas 1000 Hari Pertama Kehidupan - Julaecha Julaecha (Jurnal Abdimas Kesehatan (JAK), 2020)
The first 1000 days of life (HPK) movement is a movement to accelerate nutritional improvement. In this period the child's brain develops rapidly, although the human brain will continue to develop and can experience changes throughout life, but at this time the fastest development. The Indonesian government has committed and worked hard to accelerate the improvement of nutrition for the lives of children of the nation's next generation. The government's commitment has been stated through government regulation No. 42 of 2013 concerning the national movement to improve nutrition. Community service aims to increase the knowledge and understanding of pregnant women and mothers of children under the age of 1,000 HPK nutrition as a critical period that must be considered. Counseling method using the first 1000 days of the booklet of life published by the Ministry of Health of the Republic of Indonesia. Community service is followed by pregnant women and mothers who have toddlers in the class of pregnant women and toddlers, held in November-December 2019 at BPM Rosmala Aini. The result of this community service is an increase in maternal understanding of the importance of nutrition from pregnancy to 2-year-old children, and it is hoped that the coverage of mothers giving breastfeeding in the first hour and exclusive breastfeeding increases